Tantangan Dalam Mewujudkan Kesetaraan Gender Dalam Pers di Indonesia - Ana Nadhya Abrar (Jurnal Ilmu Sosial dan Ilmu Politik, 2004)
Bringing about gender equality in press is not easy task. It requires five conditions to be meet simultaneously: (i) amendment of Act No. 40/1999; (ii) serious implementation of Indonesian Journalists Ethics Code; (iii) increase of woman journalists; (iv) stopping discrimination agains women in society; and (v) an atmosphere of gender justice in society.